2020
DOI: 10.1128/mbio.01559-20
|View full text |Cite|
|
Sign up to set email alerts
|

How the Anaerobic Enteropathogen Clostridioides difficile Tolerates Low O 2 Tensions

Abstract: Clostridioides difficile is a major cause of diarrhea associated with antibiotherapy. After germination of C. difficile spores in the small intestine, vegetative cells are exposed to low oxygen (O2) tensions. While considered strictly anaerobic, C. difficile is able to grow in nonstrict anaerobic conditions (1 to 3% O2) and tolerates brief air exposure indicating that this bacterium harbors an arsenal of proteins involved in O2 detoxification and/or protection. Tolerance of C. difficile to low O2 tensions requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 79 publications
1
46
0
Order By: Relevance
“…The level of O 2 tolerance varies among clostridial vegetative cells and this tolerance is both strain-and mediumdependent within a species (Kawasaki et al, 1998;Hillmann et al, 2008;Edwards et al, 2016). Tolerance to O 2 with a maintained growth in liquid culture for several hours in the presence of low O 2 tension (0.2%-3%) has been described for C. acetobutylicum (O'Brien and Morris, 1971;Hillmann et al, 2008), Clostridium butyricum (Camerini et al, 2019) and C. difficile (Neumann-Schaal et al, 2018;Giordano et al, 2018b;Kint et al, 2020) even if a phase of latence is observed in C. butyricum (Kawasaki et al, 1998). Woundcolonizing clostridial species such as C. perfringens and C. tetani and Clostridium tertium isolated from gas gangrene wounds are considered to be aerotolerant (Trinh et al, 2000;Bruggemann et al, 2004;Fujitani et al, 2007).…”
Section: Various Levels Of O 2 Tolerance and Air Survival Among Clostridiamentioning
confidence: 99%
See 2 more Smart Citations
“…The level of O 2 tolerance varies among clostridial vegetative cells and this tolerance is both strain-and mediumdependent within a species (Kawasaki et al, 1998;Hillmann et al, 2008;Edwards et al, 2016). Tolerance to O 2 with a maintained growth in liquid culture for several hours in the presence of low O 2 tension (0.2%-3%) has been described for C. acetobutylicum (O'Brien and Morris, 1971;Hillmann et al, 2008), Clostridium butyricum (Camerini et al, 2019) and C. difficile (Neumann-Schaal et al, 2018;Giordano et al, 2018b;Kint et al, 2020) even if a phase of latence is observed in C. butyricum (Kawasaki et al, 1998). Woundcolonizing clostridial species such as C. perfringens and C. tetani and Clostridium tertium isolated from gas gangrene wounds are considered to be aerotolerant (Trinh et al, 2000;Bruggemann et al, 2004;Fujitani et al, 2007).…”
Section: Various Levels Of O 2 Tolerance and Air Survival Among Clostridiamentioning
confidence: 99%
“…In C . difficile , the two FDPs and revRbrs play a pivotal role in O 2 tolerance and their NAD(P)H‐dependent O 2 ‐reductase activities seem to be additive in vivo (Kint et al ., 2020). Indeed, while single mutations have no or only a weak effect on O 2 tolerance, a quadruple mutant has a strong growth defect when exposed to 0.1% O 2 and is completely unable to grow at 0.4% O 2 .…”
Section: Enzymes Involved In Oxygen Scavenging or Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that RevRbrs are O 2 - and H 2 O 2 -reductases, which have a key role to the ability of C . difficile to grow in the presence of low oxygen tension [ 54 ]. On the contrary, for CD17-146, their amount did not change at MIC/4 and decreased by half at MIC/2 ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, unlike the Enterobacteriaceae, C . difficile is an obligate anaerobe (i.e., it cannot use O 2 as a terminal electron acceptor) and is only capable of growing in the presence of relatively low levels of oxygen (<3% O 2 ), likely due to a suite of enzymes involved in detoxifying reactive oxygen species [ 97 99 ]. So, we hypothesize that if inflammation ( C .…”
Section: Toward a Better Understanding Of How C Difficile Balances Dysbiosis And Inflammation To Tmentioning
confidence: 99%